Facial reanimation using hypoglossal‐facial neurorrhaphy with end‐to‐side coaptation between the jump interpositional nerve graft and hypoglossal nerve: Outcome and duration of preoperative paralysis. Issue 6 (28th August 2015) - Okochi, Masayuki; Ueda, Kazuki; Okochi, Hiromi; Asai, Emiko; Sakaba, Takao; Kajikawa, Akiyoshi
Abstract : Background: In this report, we described the use of hypoglossal‐facial neurorrhaphy with end‐to‐side coaptation between the jump interpositional nerve graft and the hypoglossal nerve for facial reanimation and analyzed the relationship between the outcome of surgery and duration of preoperative paralysis. Methods: We performed hypoglossal‐facial neurorrhaphy with the jump interpositional nerve graft on nine men and 10 women with unilateral complete facial paralysis. The patients, with a mean age of 39.7 ± 18.1 years (range, 8–65 years) at the time of surgery, experienced preoperative paralysis ranging from 1 to 150 months (mean, 16.9 ± 34.9 months). The movement of the corners of the mouth was evaluated 12 months after surgery using a unique method based on the House–Brackmann grading scale. Results: The mean follow‐up was 5.6 ± 1.6 years (range, 3–9 years). The movement of the corners of mouth was classified as excellent in two cases, good in seven cases, fair in two cases, and poor in eight cases. Nine of the 11 cases with preoperative paralysis of 6 months or less had excellent or good results, whereas none of the eight cases with preoperative paralysis of 7 months or longer yielded excellent or good results, showing a significant difference ( P = 0.01). Conclusions: To achieve successful reanimation of the corners of the mouth, hypoglossal‐facial neurorrhaphy with end‐to‐side coaptation between the jump interpositional nerve graft and the hypoglossal nerve should be performed within 6 months after the onset of facial nerve paralysis. © 2015 Wiley Periodicals, Inc. Microsurgery 36:460–466, 2016.